Non-Pharmacological Nursing Interventions for the Prevention and Management of Delirium in Hospitalized Older Adults: Implications for Clinical Practice - Al-Badrani, -Khalid Abdullah Abdulrahman; Albanagi, Eman Abdullah Alsabi; Almutairi, Fahad Mazyad Mohammed; Alshammri, Fares Mazzi Abdallh; Alshammari, Faiz Ibraheem Hamad; Alanazi, Suad Judaya Owayed (Journal of Ecohumanism, 2024)
Background: Delirium is a common and serious neurobehavioral condition among hospitalized older adults, often leading to poor long-term outcomes. Effective management requires a multifaceted approach, including both pharmacological and non-pharmacological interventions. Methods: This systematic review evaluates non-pharmacological nursing interventions aimed at preventing and treating delirium in hospitalized older adults. A thorough search was conducted using electronic databases such as PubMed, CINAHL, Embase, and the Cochrane Central Register of Randomized Controlled Trials. The review focused exclusively on randomized controlled trials (RCTs) to ensure high-quality evidence. Results: The analysis included nine RCTs that examined various non-pharmacological interventions, ranging from multicomponent strategies to single interventions like music therapy and cognitive activities. The findings indicated that non-pharmacological interventions significantly reduce the incidence and severity of delirium in hospitalized patients. Specific strategies, such as family involvement and multimedia education, were particularly effective. However, there was variability in the timing and frequency of interventions, with most studies administering them repetitively over extended durations. Conclusion: Non-pharmacological nursing interventions are crucial for the prevention and management of delirium in older adults. This review provides a framework for nursing practice, highlighting effective strategies that nurses can implement in clinical settings. Future research should focus on standardizing intervention protocols and exploring the long-term impacts of these approaches on patient outcomes.